The Effectiveness of 0.2% Chlorhexidine Mouthwash to Reduce Dental Plaque for Students of the Department of Dental Health, Poltekkes Kemenkes Makassar - Syamsuddin Abubakar; Nurwiyana Abdullah; Bahtiar Bahtiar (Alliance oh Health Activists (AloHA), 2024)
Chlorhexidine is an antiseptic that is absorbed by the tooth surface and has antibacterial properties against organisms that try and is the most effective mouthwash to reduce plaque. Dental plaque is a soft, non-calcified layer of bacteria that accumulates and adheres to the teeth. In the form of a thin layer, dental plaque is generally invisible and can only be seen with the help of a disclosing agent. The purpose of this study was to analyze the effectiveness of 0.2% chlorhexidine mouthwash on plaque formation in students of the Department of Dental Health, Poltekkes Kemenkes Makassar 2019. This type of research was pre-experimental with a one-group pretest-posttest design. The research subjects were 30 students of Department of Dental Health, Poltekkes Kemenkes Makassar, selected by purposive sampling technique. Data on plaque before and after mouthwash was measured by plaque index. The difference in plaque index between before and after the intervention was analyzed using the Wilcoxon test. The results of the analysis showed that before the intervention, the majority of respondents had a plaque index in the good category (63%), while after the intervention, the majority of respondents also had a plaque index in the good category, with a larger proportion of 77%. Furthermore, it was concluded that 0.2% chlorhexidine mouthwash was effective in reducing plaque on teeth. Keywords: chlorhexidine 0.2%; mouthwash; plaque index